EMOSurv (utilizing visual emotion techniques survey in teaching and learning as an innovative approaches using moble applications) / Juaini Jamaludin…[et al.] - Jamaludin, Juaini; Mad Hashim, Azhari; Mamat Nawi, Azmir; Shawalludin, Syahrini; Mohd Yusof, Fadila (Universiti Teknologi MARA, Kedah, 2018)
EMOSurv Apps is a mobile application proposed as a survey instrument to conduct a survey during academic session. A traditional survey session usually will be conducted using a set of questionnaires using papers. Questionnaires are a research instruments consisting of series of questions develop for the purpose of gathering data information or feedback on some issues or opinion from respondent. The problem encountered during the survey session usually related to time constraint and to compile and arrange the data before the data can be analyse. The problem adze in traditional method includes within the use of paper questionnaires, difficulties in analysis process and its limitation for fieldwork. These problems can be reduces by using the proposed survey conducted during the academic semester and potential to be includes as one of the method in teaching and learning activity.